A TASK-BASED TRAINING PROGRAM TO IMPROVE ACADEMIC WRITING SKILLS AMONG FIRST-YEAR STUDENTS - Rezki Amelia; Gusmirawati Gusmirawati; Reni Novianti Sari; Intan Kumalasari; M. Ilham Lutfi; Sri Karyani Damanik (MEDIA INOVASI PENDIDIKAN DAN PUBLIKASI, 2026)
Academic writing skills are fundamental competencies that must be mastered by students from the beginning of higher education. However, first-year students commonly encounter various challenges in academic writing, including weak text organization, inappropriate use of academic language, limited argument development, and insufficient understanding of citation practices and academic ethics. This program aimed to strengthen the academic writing skills of first-year university students through a task-based approach. The program employed a service-learning method implemented through participatory stages, including needs analysis, training sessions, step-by-step writing practice, mentoring, and reflective evaluation. Data were collected through observation, analysis of students’ writing tasks, and participant reflections, and were analyzed using a descriptive qualitative approach. The results show a significant improvement in students understanding of academic writing concepts and characteristics, enhanced writing quality in terms of structure, language use, and argumentation, as well as increased awareness of citation practices and academic integrity. In addition, the program positively influenced students’ attitudes and motivation toward academic writing. These findings suggest that academic writing training based on a task-based approach is effective in strengthening first-year students’ academic literacy and has the potential to be developed as a model for fostering academic culture in higher education institutions.